Pendampingan UMKM Gethuk Frozen ‘Sri Gethuk’ melalui Sertifikasi Halal dan Inovasi Kemasan sebagai Strategi Penguatan Daya Saing Produk Lokal di Desa Watuaji - Miswan Ansori; Fadia Risqi Dwiyanti; Muhammad Junaidi Retno Manggolo; Muhammad Ichsan syarifudin; Andika Febrian Pratama; Fatjri Rohman; M. Azrul Aditya Saputra; Ahmad Septian Eka Setiawan; Salma Mufarrikhatul Walidiyah; Linda listiyani; Aniqotun Zukhanid; Febrina Eka Zunita; Qoriatul Hikmah; Risma Hanifatur Rosyida; Mufidah Lu’lu’ah; Syarifatul Wardah; Qodriyatul Alfiyah (Profetik: Jurnal Pengabdian Masyarakat, 2025)
The community service program for UMKM Gethuk Frozen ‘Sri Gethuk’ in Watuaji Village, Keling District, Jepara Regency, was carried out through halal certification and packaging innovation as a strategy to strengthen the competitiveness of local products. This program was motivated by the limited access of the UMKM to modern markets due to the lack of halal certification and the use of simple packaging. The aim of the service is to enhance product legality, quality, and attractiveness through a participatory problem-solving approach. Implementation methods included field observation, halal certification socialization and education, guidance in document preparation, facilitation of certification by the service team, packaging design development, and monitoring and evaluation. Results indicate that with active facilitation, the UMKM successfully obtained halal certification, improved packaging quality to be more appealing and informative, and implemented better production standards. The program’s impact is evident in increased consumer trust, expanded market access, and improved internal capacity of the UMKM. Thus, this program successfully strengthens the competitiveness of local products and empowers the UMKM sustainably.